Optical coherence tomography and its role in the diagnosis of ocular hypertension, preperimetric and perimetric glaucoma - B. Angelov; K. Petrova (Oftalʹmologiâ)
Aim. To study diagnostic capabilities of OCT parameters (ganglion cell complex/GCC and retinal nerve fiber layer/RNFL) and their ability to discriminate between normal and ocular hypertension (OH), preperimetric glaucoma (PPG), and early, moderate, and advanced perimetric glaucoma (PG) eyes. Material and methods. 353 eyes enrolled in the study were divided into six groups: OH (32 eyes), PPG (46 eyes), early PG (104 eyes), moderate PG (54 eyes), advanced PG (60 eyes), and healthy individuals (57 eyes). Complete eye examination including standard automated perimetry and OCT was performed. Avg. GCC, Inf. GCC, Sup. GCC, GLV, FLV, and Avg., Sup. and Inf. RNFL (ONH map) were measured. ROC curves were constructed. Sensitivity and specificity of each parameter, positive (PLR) and negative likelihood ratio (NLR) were analyzed. Results. In OH group, sensitivity and specificity of all parameters were above 66% (> 98% for FLV and GLV). In PPG group, sensitivity and specificity were above 82% (>91% for GLV, Avg. GCC Avg. RNFL and Sup. RNFL). In OH group, GLV and Inf. GCC were the most accurate diagnostic parameters (0.795 and 0.790, respectively). In PPG group, GLV was the most accurate diagnostic parameter (0.981). In early PG group, maximum sensitivity and specificity were found for Inf. GCC (91%). In moderate PG group, maximum sensitivity and specificity were found for the Avg. GCC (98%). In early and moderate PG groups, GLV was the most accurate diagnostic parameter (0.971 and 0.999, respectively). In advanced PG group, sensitivity and specificity of all parameters were about 100%. In advanced PG groups, Avg. RNFL and Inf. RNFL were the most accurate diagnostic parameters (1.0). Conclusions. In PPG and PG groups, high sensitivity and specificity of GCC map and RNFL map parameters as well as their very high diagnostic accuracy (more than 0.90) was demonstrated. In OH group, the diagnostic accuracy of these parameters was lower (0.66). GCC map and RNFL map parameters are characterized by high and comparable diagnostic abilities irrespective of glaucoma damage severity. ОСТ is a valuable diagnostic method of early glaucomatous changes detection in OH and PPG. Diagnostic capabilities of the parameters improve as disease severity increases.